The background of Silariang marriage in Datara Village, Bontoramba District, Jeneponto Regency. - Yusri, Muh.; Amin, Muliaty; Kasman, Suf (Jurnal Mercusuar, 2021)
This journal examines the impact of Silariang marriage on families in Datara Village, Bontoramba District, Jeneponto Regency. The purpose of this research is to determine the background of the occurrence of Silariang marriage in Datara Village, Bontoramba District, Jeneponto Regency. This qualitative descriptive study uses an Islamic Dawka approach. The data sources used are primary sources, including information from Silariang marriage books and direct observation at the research location, as well as secondary sources obtained from documentation and literature studies to supplement primary data. Data collection is carried out through observation, interviews, and documentation, and data processing and analysis are carried out through three stages: data reduction, data presentation, and conclusion drawing. The research results indicate that the factors behind Silariang marriage in Datara Village, Bontoramba District, Jeneponto Regency are: 1. Opposing arranged marriage (forced marriage), 2. Economic factors, 3. Traditional social interactions, 4. Differences in social strata.